Effect of Health Education Using Audiovisual Media on Increasing Adolescent Knowledge in Preventing Vape Use at SMPN 6 Surabaya - Zhafilla Claudia; Siti Nur Kholifah; Irfany Nurul Hamid; Joko Suwito (International Journal of Advanced Health Science and Technology, 2025)
ABSTRACT Teenagers are vulnerable to smoking habits, including the trend of using vapes which is attractive because of its various flavors and designs. However, vaping is at risk of causing lung disease, heart disease, brain development disorders, and nicotine addiction. Prevention is carried out by increasing adolescent knowledge through health education using audiovisual media . This study is a quasi-experimental study with one group pretest-posttest design, the research population was adolescents at SMPN 6 Surabaya. The research sample was 186 adolescents with random sampling technique. Data collection using a questionnaire on the level of knowledge, attitudes, and actions while data analysis using the Wilcoxon test . The results of the study of knowledge before being given health education showed that adolescents had sufficient behavior in preventing vape use . While knowledge after being given health education showed that adolescents had good knowledge in preventing vape use . There is a significant difference between adolescent knowledge in preventing vape use before and after being given education with audiovisual media. This should be the main focus of health workers who of course need to be assisted by schools and families in providing education regarding the dangers of vape use for adolescents. Likewise, adolescents are expected to become individuals who are more aware of the importance of maintaining health and are able to make decisions. KEYWORDS Health Education, Audiovisual Media, Knowledge Level, Prevention of Vape Use , Adolescents